Acquired infections in paediatric patients after cardiac surgery - Appel, Ilse Nadine (Department of Paediatrics and Child Health, 2016)
Introduction: Hospital acquired infections (HAIs) are an important cause of morbidity and mortality following paediatric cardiac surgery. Aim: To determine the incidence, risk factors for and outcome of postoperative HAIs in the Paediatric Intensive Care Unit (PICU) of the Red Cross War Memorial Children's Hospital (RCWMCH) in Cape Town. Methods: A prospective observational study of all postoperative cardiac patients admitted to PICU from September 2011 to March 2012. The definitions of laboratory confirmed blood stream infections (BSI), urinary tract infections (UTI), and surgical site infections were based on the Centres of Disease Control criteria. Ventilator associated pneumonia (VAP) was diagnosed using a modification of the Clinical Pulmonary Infection Score (CPIS). Results: 110 patients (median age 19 months; 43% male) undergoing 126 surgical procedures were enrolled. Sixty HAIs occurred in 43 (39%) patients (68.3% pulmonary; 13.3% blood; 11.7% wound; 3.3% urine; 3.3% tissue). Nine (8.2%) patients died and their deaths were not related to HAIs.